(untitled) (Third Sector Social Economic Review, 2026)
The study aims to evaluate and compare the environmental sustainability performance of two companies operating in the iron and steel sector within the same corporate group. For this purpose, the environmental sustainability performance of İSDEMİR and ERDEMİR between 2021 and 2024 was assessed, the companies were compared both individually and with each other. The study employed the Multi-Criteria Decision-Making (MCDM) methods of LOgarithmic Percentage Change-driven Objective Weighting (LOPCOW), COmpromise Ranking from Alternative SOlutions (CORASO), and Ranking Alternatives by Perimeter Similarity (RAPS). In order to determine the criteria to be used in the evaluation, a literature review was conducted in the Web of Science (WoS) and Scopus databases. According to the criterion weights calculated using the LOPCOW method, the most important criterion is the total amount of waste, the least important is the amount of recycled water. When the results of the CORASO and RAPS methods used to rank the companies based on their environmental sustainability performance are examined, it is observed that the methods generally produce similar rankings, and that the correlation between them is quite high. When the ranking results of both methods are evaluated together, it is revealed that ERDEMİR’s environmental sustainability performance was higher between 2021 and 2024, while İSDEMİR’s performance showed improvement over time. As a result of the sensitivity analysis, it was revealed that the models used are robust and reliable. In addition, it was determined that the methods are sensitive to changes in criterion weights.